Jumping to conclusions at first onset of psychosis predicts longer admissions, more compulsory admissions and police involvement over the next 4 years: the GAP study. Issue 13 (5th November 2018) - Rodriguez, Victoria; Ajnakina, Olesya; Stilo, Simona A.; Mondelli, Valeria; Marques, Tiago Reis; Trotta, Antonella; Quattrone, Diego; Gardner-Sood, Poonam; Colizzi, Marco; Wiffen, Benjamin D.; Dazzan, Paola; Di Forti, Marta; et al.
Abstract: Background: Jumping to conclusions (JTC), which is the proneness to require less information before forming beliefs or making a decision, has been related to formation and maintenance of delusions. Using data from the National Institute of Health Research Biomedical Research Centre Genetics and Psychosis (GAP) case–control study of first-episode psychosis (FEP), we set out to test whether the presence of JTC would predict poor clinical outcome at 4 years. Methods: One-hundred and twenty-three FEP patients were assessed with the Positive and Negative Syndrome Scale (PANSS), Global Assessment of Functioning (GAF) and the probabilistic reasoning 'Beads' Task at the time of recruitment. The sample was split into two groups based on the presence of JTC bias. Follow-up data over an average of 4 years were obtained concerning clinical course and outcomes (remission, intervention of police, use of involuntary treatment – the Mental Health Act (MHA) – and inpatient days). Results: FEP who presented JTC at baseline were more likely during the follow-up period to be detained under the MHA [adjusted OR 15.62, 95% confidence interval (CI) 2.92–83.54, p = 0.001], require intervention by the police (adjusted OR 14.95, 95% CI 2.68–83.34, p = 0.002) and have longer admissions (adjusted IRR = 5.03, 95% CI 1.91–13.24, p = 0.001). These associations were not accounted for by socio-demographic variables, IQ and symptom dimensions. Conclusions: JTC in FEP is associated with poorer outcome as indicated and defined by more compulsion police intervention and longer periods of admission. Our findings raise the question of whether the implementation of specific interventions to reduce JTC, such as Metacognition Training, may be a useful addition in early psychosis intervention programmes.